Low access to a highly effective therapy: a challenge for international tuberculosis control - Dye Christopher; Watt Catherine J.; Bleed Daniel (The World Health Organization, 2002)
OBJECTIVE: To determine the scale of the tuberculosis (TB) problem facing the international Stop TB Partnership by measuring the gap between present rates of case detection and treatment success, and the global targets (70% and 85%, respectively) to be reached by 2005 under the WHO DOTS strategy. METHODS: We analysed case notifications submitted annually to WHO from up to 202 (of 210) countries and territories between 1980 and 2000, and the results of treatment for patients registered between 1994 and 1999. FINDINGS: Many of the 148 national DOTS programmes in existence by the end of 2000 have shown that they can achieve high treatment success rates, close to or exceeding the target of 85%. However, we estimate that only 27% of all the new smear-positive cases that arose in 2000 were notified under DOTS, and only 19% were successfully treated. The increment in case-finding has been steady at about 133 000 additional smear-positive cases in each year since 1994. In the interval 1999- 2000, more than half of the extra cases notified under DOTS were in Ethiopia, India, Myanmar, the Philippines, and South Africa. CONCLUSION: With the current rate of progress in DOTS expansion, the target of 70% case detection will not be reached until 2013. To reach this target by 2005, DOTS programmes must find an additional 333 000 cases each year. The challenge now is to show that DOTS expansion in the major endemic countries can significantly accelerate case finding while maintaining high cure rates.